Associations between TNFSF4 gene polymorphisms (rs2205960 G > A, rs704840 T > G and rs844648 G > A) and susceptibility to autoimmune diseases in Asians: a meta-analysis. (17th February 2021) - Yang, Yangyang; Li, Xiahui; Li, Bowen; Mu, Liying; Wang, Jin; Cheng, Yunmeng; Gu, Yao; Wu, Huijian
ABSTRACT: Background: Tumor necrosis factor superfamily member 4 (TNFSF4) has significant role in modulating autoimmune diseases (ADs) and single nucleotide polymorphism (SNP) is also related with the susceptibility to some diseases. So a meta-analysis aimed at systematically assessing the associations between TNFSF4 polymorphisms (rs2205960 G > A, rs704840 T > G and rs844648 G > A) and ADs risk was performed in Asians. Methods: Total 14 eligible articles published before March 2019 involving 35 studies, of which 21 studies (16, 109 cases and 26, 378 controls) for rs2205960 G > A, 8 studies (2, 424 cases and 3, 692 controls) for rs704840 T > G, and 6 studies (3, 839 cases and 5, 867 controls) for rs844648 G > A were included. Effects of the three respective polymorphisms on the susceptibility to ADs were estimated by pooling the odds ratios (ORs) with their corresponding 95% confidence interval (95% CI) in allelic, dominant, recessive, heterozygous and homozygous models. Results: The overall analysis revealed that all the rs2205960 G > A, rs704840 T > G and rs844648 G > A polymorphisms could increase the risk of ADs in allelic, dominant, recessive, heterozygous and homozygous models. Furthermore, subgroup analysis showed that both rs2205960 G > A and rs704840 T > G were significantly associated with the susceptibility to systemic lupus erythematosus (SLE). What's more, statistically significant association between rs2205960 G > A polymorphism and primary Sjögren's syndrome (pSS) susceptibility was also observed in allelic, dominant and heterozygous models. Conclusions: This current meta-analysis suggested that all of the three TNFSF4 polymorphisms may be associated with ADs susceptibility in Asians.